âEVALUASI IMPLEMENTASI KEBIJAKAN REFORMASI BIROKRASI KEMENTERIAN KOORDINATOR BIDANG PEREKONOMIANâ - Mulyadi, Mulyadi (issn 1978-6573, 1978)
Abstract The study aims at revealing the legal basis and the purpose of bureaucracy reform; explaining the program, strategy, and human resource; explaining the execution and implementation of bureaucracy reform policy along with its result and impacts. This study is implemented at the Coordinating Ministry for Economic Affairs. This study is conducted by using combination of Contex, Input, Process and Product (CIPP) Evaluation by Daniel L.Stufflebeam and Analysis Evaluation Model System (MESA) which was firstly used by Kard Luwig Bertaalanffy. Data collection is conducted throught interview, study on relevant documents, and observation. The result of the study indicates that: 1) The legal basis used needs more improvement; 2) The implementation of bureaucracy reform has been moving towards a professional bureaucracy, integrity, high performance, neutral and prosperous; 3) bureaucracy reform process needs to be accelerated; 4) bureaucracy reform policy could be continued with some revisions. The results of this study are expected to give benefits for execution and expansion of bureaucracy reform under Ministry Coordinating for the Economic Affair and national.Key Words:bureaucracy reform, policy,evaluation RINGKASAN Tujuan reformasi birokrasi Kementerian Koordinator Bidang Perekonomian adalahuntuk menjadikan birokrasi Pemerintah yang profesional, berintegritas, berkinerja tinggi, bersih dan bebas korupsi, kolusi dan nepotisme, mampu melayani stake holder/pemangku kepentingan dengan baik, netral, sejahtera, berdedikasi, dan memegang teguh nilai-nilai dasar serta kode etik pengawai negeri sipil.Tujuan Penelitian ini adalah untuk mengetahui efektifitas kinerja birokrasi. Penelitian ini menggunakan penggabungan model evaluasi Contex, Input, Process, dan Product (CIPP) oleh Daniel L. Stufflebeam danSystem Analysis Evaluation Model/ Model Evaluasi Sistim Analisis (MESA), model ini pertama kali digunakan oleh Kard Luwig Bertaalanffy. Pengumpulan data dilakukan dengan wawancara, studi dokumen dan observasi. Hasil penelitian menunjukkan bahwa 1) Dasar hukum yang digunakan masih perlu disempurnakan. 2) pelaksanaan reformasi birokrasi telah menuju kearah birokrasi yang profesional, berintegritas, berkinerja tinggi, dan netral. 3) proses reformasi birokrasi perlu dipercepat. 4) kebijakan reformasi birokrasi dapat diteruskan dengan beberapa perbaikan. Hasil penelitian ini diharapkan membawa manfaat bagi pelaksanaan dan perluasan reformasi birokrasi di kementerian koordinator bidang perekonomian dan nasional.Kata Kunci: reformasi birokrasi, kebijakan, evaluasi